Origin of enhanced piezoelectric energy harvesting in all-polymer-based core–shell nanofibers with controlled shell-thickness. (15th October 2021) - Han, Ju; Kim, Ji Ho; Choi, Hong Je; Kim, Seung Won; Sung, Sun Min; Kim, Min Sung; Choi, Bo Kyoung; Paik, Jong Hoo; Lee, Joon Seok; Cho, Yong Soo
Abstract: Polymer nanofiber-based piezoelectric composites have been actively investigated as ideal energy generators for low-power-consuming electronic devices. Herein, we introduce a core–shell nanofiber-based piezoelectric energy harvester consisting of poly (vinylidene fluoride-trifluoroethylene (P(VDF-TrFE)) as a piezoelectric shell and poly (3, 4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) as a conductive core, which was optimized primarily by adjusting the relative shell thickness. The thinnest shell layer exhibited the best output performance, i.e., ~8.76 V and ~547 nA, which correspond to the 10-fold and 5-fold increases relative to the reference values for only P(VDF-TrFE) nanofibers. Almost doubled performance of ~13.2 V and ~950 nA was further achieved by connecting two harvesters in series and parallel, respectively. Origin of the harvesting enhancements was believed to be associated with extra space-charge polarization and the content of β-phase. The core-shell devices were also successfully demonstrated as tactile sensors to electrically detect various body motions. Graphical abstract: Image 1 Highlights: A conductive core-piezoelectric shell composite nanofibers were produced. The core-shell harvesters were prepared at room temperature by printing. A thinner shell layer created better piezoelectric energy harvesting performance. The best performance with optimal structure reached ~13.2 V and ~950 nA. Extra interfacial polarization with more beta-phase contributed to the harvesting.